(untitled) (Al-Aasar, 2025)
This study critically assesses the impact of Islamic microfinance (IMF) on poverty alleviation in rural Pakistan, an area characterized by persistent socio-economic challenges. Employing a qualitative research design through secondary data analysis, this research synthesizes findings from an extensive body of existing literature, including academic journals, institutional reports, and policy documents. The study investigates the operational models of Islamic microfinance institutions (IMFI) in rural Pakistan, their contributions to income generation, asset building, and household welfare, and their social impacts, particularly concerning women’s empowerment. Furthermore, it identifies the specific challenges and limitations faced by IMFI in achieving their poverty alleviation objectives. Initial findings from the literature suggest that while IMFI, such as Akhuwat and NRSP, have made commendable strides in providing Shariah-compliant financial services, particularly Qard al-Hasan (interest-free loans), their overall impact on deep-rooted poverty in rural Pakistan warrants a nuanced and critical examination. The analysis reveals both promising outcomes in financial inclusion and livelihood enhancement, alongside significant hurdles related to outreach, sustainability, and potential mission drift. This assessment aims to provide comprehensive insights for policymakers and practitioners to enhance the effectiveness and outreach of Islamic microfinance for sustainable poverty alleviation in the region.